Firms of endearment : how world-class companies profit from passion and purpose - Sisodia, Rajendra (Pearson Education, 2014)
Today's best companies get it. From retail to finance and industries in between, the organizations who recognize that doing good is good business are becoming the ultimate value creators. They're changing their culture and generating every form of value that matters: emotional, experiential, social, and financial. And they're doing it for all their stakeholders. Not because it's simply politically correct, because it's the only path to long-term competitive advantage. These are the firms of endearment . Companies people love doing business with, working for and collaborating with as partners. Since the publication of the First Edition, the concept of corporate social responsibility has become embraced as a valid, important, and profitable business model. It is a trend that has transformed the workplace and corporate world.¿ This Second Edition updates the examples, cases, and applications from the original edition, giving readers insight into how this hallmark of the modern organization is practiced today.